2022
DOI: 10.3390/children9081253
|View full text |Cite
|
Sign up to set email alerts
|

Novel Lung Growth Strategy with Biological Therapy Targeting Airway Remodeling in Childhood Bronchial Asthma

Abstract: Anti-inflammatory therapy, centered on inhaled steroids, suppresses airway inflammation in asthma, reduces asthma mortality and hospitalization rates, and achieves clinical remission in many pediatric patients. However, the spontaneous remission rate of childhood asthma in adulthood is not high, and airway inflammation and airway remodeling persist after remission of asthma symptoms. Childhood asthma impairs normal lung maturation, interferes with peak lung function in adolescence, reduces lung function in adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 143 publications
0
1
0
Order By: Relevance
“…The findings of a 50 year cohort study demonstrate a significant association between pediatric asthma and an increased risk of developing COPD in later life ( 53 ); children with a prior history of asthma exhibit a 3.45-fold increased likelihood of developing COPD compared to children without such a medical background ( 54 ). Pediatric asthma can impair lung development, hindering the attainment of normal peak lung function during adolescence and diminishing adult lung function, thereby augmenting the susceptibility to developing COPD ( 55 ). Nevertheless, early suppression of airway inflammation and prevention of asthma exacerbations in childhood can foster optimal lung development and maturation, culminating in enhanced lung function and a reduced risk of COPD in adulthood ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of a 50 year cohort study demonstrate a significant association between pediatric asthma and an increased risk of developing COPD in later life ( 53 ); children with a prior history of asthma exhibit a 3.45-fold increased likelihood of developing COPD compared to children without such a medical background ( 54 ). Pediatric asthma can impair lung development, hindering the attainment of normal peak lung function during adolescence and diminishing adult lung function, thereby augmenting the susceptibility to developing COPD ( 55 ). Nevertheless, early suppression of airway inflammation and prevention of asthma exacerbations in childhood can foster optimal lung development and maturation, culminating in enhanced lung function and a reduced risk of COPD in adulthood ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric asthma can impair lung development, hindering the attainment of normal peak lung function during adolescence and diminishing adult lung function, thereby augmenting the susceptibility to developing COPD (55). Nevertheless, early suppression of airway inflammation and prevention of asthma exacerbations in childhood can foster optimal lung development and maturation, culminating in enhanced lung function and a reduced risk of COPD in adulthood (55). In a cross-sectional survey conducted on 851 patients with chronic sinusitis in seven cities across China, the prevalence of Chronic sinusitis Frontiers in Medicine 09 frontiersin.org among individuals with asthma was observed to be 24%, which is significantly higher compared to the 7% prevalence found among non-asthmatic participants (56).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, recent data focusing on severe non-eosinophilic forms of asthma have shown that neutrophils, inflammatory cytokines and/or mesenchymal cells may play a decisive role in the severity and progression of the disease [ 7 , 51 , 52 , 53 , 54 , 55 ]. In the same context, studies have supported that disease progression in adulthood may be predisposed by repeated exacerbations of asthma in childhood [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The available studies have been conducted only in adults and in small size samples, showing a potential in vivo effect in airway remodeling evaluated through CT (omalizumab [75][76][77] and mepolizumab [78]) with a reduction in airway wall thickness and wall area, and increase in the tracheal lumen area, and through bronchial biopsies (omalizumab [79][80][81] and benralizumab [82]) with a reduction in reticular basement membrane thickness, in airway smooth muscle proteins, and in fibronectin deposit in airway submucosa. To date, no studies are available on the in vivo effects of dupilumab on airway remodeling [83]. Furthermore, even after discontinuation, biologic therapies possibly induce better control of asthma, thanks to their effect on airway remodeling.…”
Section: Evolution Of Childhood Asthma After Prolonged Biological Tre...mentioning
confidence: 99%